The rice economy of Asia - Barker, Randolph (Resources for the Future, 1985)
The book presents a comprehansive picture of the role of rice in the food and agricutural sectors of Asian nations. Rica is a dominant consumption good, an important employer of resources, astrong polical focal point and the beneficiary of considerable research attention. To millions, rice is the center of existence, and more the percent of the world's rice is produced in Asia.